Smurf1 silencing restores PTEN expression that ameliorates progression of human glioblastoma and sensitizes tumor cells to mTORC1/C2 inhibitor Torin1 - Qin Xia; Wenxuan Li; Sakhawat Ali; Mengchuan Xu; Yang Li; Shengzhen Li; Xinyi Meng; Liqun Liu; Lei Dong (iScience, 2021)
Summary: Amplification of ubiquitin E3 ligase Smurf1 promotes degradation of PTEN leading to hyperactivation of the Akt/mTORC1 pathway. However, inhibitors of this pathway have not hitherto yielded promising results in clinical studies because of strong drug resistance. Here, we investigated Smurf1 expression in various glioblastoma (GB) cell lines and patient tissues. The therapeutic efficacy of Smurf1 silencing and Torin1 treatment was assessed in GB cells and orthotopic mouse model. We found Smurf1 loss elevates PTEN levels that interrupt the epidermal growth factor receptor pathway activity. Cotreatment with Smurf1 silencing and mTORC1/C2 inhibitor Torin1 remarkably decreased phosphorylation of Akt, and mTORC1 downstream targets 4EBP1 and S6K resulting in synergistic inhibitory effects. Smurf1 knockdown in orthotopic GB mouse model impaired tumor growth and enhanced cytotoxicity of Torin1. Together, these findings suggest a rational combination of Smurf1 inhibition and Torin1 as a promising new avenue to circumvent PI3K/Akt pathway-driven tumor progression and drug resistance.